Risiko Strategi Jemput Bola Pada Produk Simpanan Sembako (SIMKO) Di KSSPS Artha Yasmin Az-zahra Jepara - Nasiroh, Ulyatin; Wahidullah, Wahidullah; Nafisah, Zahrotun (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
This research aims to explain the risks of the ball picking strategy implemented at KSPPS Artha Yasmin Az-zahra Jepara. This research uses a qualitative approach method. The pick-up strategy is very popular with cooperatives and the community because the pick-up carried out by cooperatives it's easier for people to do it transactions with the cooperative. Picking up the ball can also make it easier for people not needing to go to the workplace since it can be done at home or at the market. From the results of this research, several things have been discovered, namely the risks experienced and the strategies that have been determined for the product. In this basic food savings product, people are also very happy about this product because it is a basic food savings product. Cooperatives also experience risks in the form of late payments. It is important for KSPPS to carry out regular evaluations and improvements in the implementation of strategy to ensure sustainability and growth cooperatives in the future. Keywords: Risk, ball picking strategy, Grocery savings products,KSPPS